Information Retrieval + X → Information Assimilation - Jana, Sibsankar (Journal of Information and Knowledge, 2013)
In the present study, an attempt has been taken to develop a comprehensive model for information assimilation. Actually it is named as "Information Assimilation Cycle". Before going through the actual study, background of the study is described. At the conclusion some problems/factors associated with the assimilation have been pointed out so that we can remove these problems to attain effective information assimilation.